Upaya Strategis dalam Meningkatkan Keterampilan Berseni Siswa Kelas Tinggi di SD Laboratorium UPI Cibiru - Robi'ah, Fajriyatur; Hidayah, Nurul (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
This study aims to examine how art activities in elementary school can affect students'' art skills. To answer this question, the author conducted test by organizing a musical drama performance for high school students at SD Laboratorium UPI Cibiru. The researcher used qualitative method with observation and journal review techniques used to process data from the test results that have been carried out. The results showed that there is an impact of art activities. The test results also revealed that students have access to channel their skills in art through the organized performance activities. However, the visible potential was not followed up by the school in developing it into a competency. From an arts perspective, this study emphasizes the access for students to channel and develop their skills in art. Keywords : Art, High Grade, Elementary School, Musical Drama And Skills